2019
DOI: 10.1121/1.5092213
|View full text |Cite
|
Sign up to set email alerts
|

Effects of flow recirculation on unmanned aircraft system (UAS) acoustic measurements in closed anechoic chambers

Abstract: An experimental campaign was undertaken to identify the effects of flow recirculation on an isolated rotor's acoustic emissions in a closed anechoic chamber. It is shown that flow recirculation results in a significant increase in higher harmonic noise, with an increase of more than 15 dB in some harmonics. This increase in noise is due to the nature of testing in a closed facility and does not represent the acoustic emissions of a similar rotor in hovering flight outdoors. Future measurements of rotors and fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(14 citation statements)
references
References 3 publications
1
13
0
Order By: Relevance
“…9-14 However, the BPF higher harmonics are less pronounced than in some of the other data. Stephenson and coworkers 33,42 suggested that flow recirculation in a closed chamber can increase the magnitude of BPF harmonics (in line with other studies 53 ). With our test set-up comprising a rotor-wall clearance of at least ∼ 8D p to all sides (except for the ground plane at ∼ 4D p clearance), this flow recirculation effect may be minor with, as a consequency, a lower-magnitude higher harmonic noise content (e.g.…”
Section: Acoustic Field Characteristicssupporting
confidence: 62%
See 2 more Smart Citations
“…9-14 However, the BPF higher harmonics are less pronounced than in some of the other data. Stephenson and coworkers 33,42 suggested that flow recirculation in a closed chamber can increase the magnitude of BPF harmonics (in line with other studies 53 ). With our test set-up comprising a rotor-wall clearance of at least ∼ 8D p to all sides (except for the ground plane at ∼ 4D p clearance), this flow recirculation effect may be minor with, as a consequency, a lower-magnitude higher harmonic noise content (e.g.…”
Section: Acoustic Field Characteristicssupporting
confidence: 62%
“…Fig. 4 of Stephenson et al 42 ) in comparison to other studies conducted with more confined setups. This explanation is speculative for the time-being, as no flow measurements were performed.…”
Section: Acoustic Field Characteristicsmentioning
confidence: 74%
See 1 more Smart Citation
“…Turbulent inflow noise can be predicted using a computational method such as that described in [21] or analytical methods such as that described by [22]. Note that tests conducted in anechoic chambers or confined spaces will produce a recirculating flow, which can produce high levels of turbulent inflow noise [23,24]; •…”
mentioning
confidence: 99%
“…Experimentalists studying the noise of unmanned aerial systems (UAS) take caution to ensure that noise due to recirculation of their own turbulent wake does not dominate noise measurements conducted in enclosed areas. 155157 That research, along with other recent research, 158,159 suggest that ingestion noise can contribute significantly to UAS noise. Thus this is an important area for future research, which could also have some relevance for eVTOL aircraft.…”
Section: Broadband Noisementioning
confidence: 71%